Technique for assessing reliability of insurance companies - Voronova, Irina (Business, Management and Economics Engineering, 2011)
The purpose of this study is to improve the research technique for assessing the reliability of non-life insurance companies’ position. In this study, the author considers problems of assessment of reliability of insurance companies’ position. The author analyses indicators enabling to make complex assessment of insurance companies’ reliability. A technique of creating an integral indicator by using different methods of determining weighting rates of ratios validity is offered. Practical example of using an integral indicator of reliability of Latvian non-life insurance companies on the basis of public information is introduced. Rating is a risk indicator for potential consumers of insurance services. The offered technique may serve as an instrument for analysis of the reserves for enhancing reliability and competitiveness of insurance companies.